Analisis Yuridis Pengalihan Aset Investasi Kepada Pihak Ketiga pada Aplikasi Bibit - Yona Nova Intan Perdani; Ida Nadirah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The development of financial technology has accelerated the growth of digital investment platforms, including online mutual fund applications such as Bibit, which have expanded public access to investment activities. However, this convenience also raises legal issues, particularly regarding the transfer of investment assets to third parties without proper procedures or the explicit consent of account holders. This study aims to analyze juridically the transfer of investment assets in the Bibit application by examining the validity of legal relationships, the responsibility of business actors, and investor protection. This research employs a normative legal method using statutory and conceptual approaches. The primary legal sources include the Indonesian Civil Code (KUHPerdata), the Capital Market Law, and the Consumer Protection Law. The findings indicate that the transfer of digital investment assets is legally valid only if it fulfills the requirements of Article 1320 of the KUHPerdata, obtains the explicit consent of the account holder, and complies with the principles of prudence and transparency. Any transfer conducted without the owner’s consent or without proper legal procedures constitutes an Unlawful Act (Perbuatan Melawan Hukum/PMH) under Article 1365 of the KUHPerdata. Consequently, platform providers may bear civil liability for investor losses, making regulatory strengthening and transparency essential to ensure legal certainty and investor protection.